2021
DOI: 10.14309/ctg.0000000000000309
|View full text |Cite
|
Sign up to set email alerts
|

Age at Diagnosis Is Determinant for the Outcome of Inflammatory Bowel Disease: Is It a Myth?

Abstract: INTRODUCTION: Patients with elderly-onset inflammatory bowel disease were previously associated with a less aggressive course of the disease. However, there are conflicting data that need further validation. We aimed to determine the association between age at diagnosis and the development of progressive disease in patients with Crohn's disease (CD) and ulcerative colitis (UC). METHODS: This cohort study included patients with CD and UC followed in 6 secondary and terti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…27 Similarly, younger patients diagnosed with CD have an increased risk for surgery and poor outcomes. 7,16 In addition, although the difference was not statistically significant, the number of patients who underwent ≥ 2 surgeries was higher in the early-onset group (9.5%) than in the adult-onset (5.8%) and late-onset (1.1%) groups. Because the early-onset intestinal BD group had a higher risk for intestinal surgery than the adult-onset or late-onset groups, clinicians should strictly control inflammation in the early-onset intestinal BD group.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…27 Similarly, younger patients diagnosed with CD have an increased risk for surgery and poor outcomes. 7,16 In addition, although the difference was not statistically significant, the number of patients who underwent ≥ 2 surgeries was higher in the early-onset group (9.5%) than in the adult-onset (5.8%) and late-onset (1.1%) groups. Because the early-onset intestinal BD group had a higher risk for intestinal surgery than the adult-onset or late-onset groups, clinicians should strictly control inflammation in the early-onset intestinal BD group.…”
Section: Discussionmentioning
confidence: 89%
“…Thiopurines are relatively effective in maintaining clinical remission and preventing postoperative recurrence. 35,36 Similarly, patients with CD, who were diagnosed at a younger age, have a higher risk for complicated diseases, 15,16 such as strictures, relapse, surgery, and even mortality, suggesting that young age is an independent predictive factor for poor prognosis. Lower drug compliance in younger patients, 37 diminished CD-4-mediated and CD-8-mediated immune response, 38,39 and decreased new lymphocyte production in patients with advanced age 15 have often been considered the causes of poor disease prognosis in young patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study had indicated that age at diagnosis could affect the outcome of elderly-onset CD patients. 6 It had been found that early-onset CD was different from late-onset CD in clinical outcomes and nutritional status. 7 In addition, the lifetime costs of CD patients were associated with their age at diagnosis.…”
Section: Introductionmentioning
confidence: 99%